Postnatal knockout of beta cell insulin receptor impaired insulin secretion in male mice exposed to high-fat diet stress. (1st January 2020) - Oakie, Amanda; Zhou, Liangyi; Rivers, Sydney; Cheung, Christy; Li, Jinming; Wang, Rennian
Abstract: The presence of insulin receptor (IR) on insulin-secreting beta cells suggests an autocrine regulatory role for insulin in its own signalling. Congenital beta cell-specific IR knockout (βIRKO) mouse studies have demonstrated the development of age-dependent glucose intolerance. We investigated the role of beta cell IR signalling specifically during postnatal life following undisturbed prenatal pancreatic development and maturation. We utilized a tamoxifen-inducible mouse insulin 1 promoter (MIP) driven Cre recombinase IR knockout mouse model (MIP-βIRKO) to achieve partial knockout of IR in islets and determine the functional role of beta cell IR in adult mice fed a control normal diet (ND) or 60% high-fat diet (HFD). At 24 weeks of age, MIP-βIRKO ND mice maintained glucose tolerance, insulin release, and unchanged beta cell mass when compared to control ND mice. In contrast, 24-week-old MIP-βIRKO mice demonstrated significant glucose intolerance and lower insulin release after 18 weeks of HFD feeding. A reduction in beta cell soluble N -ethylmaleimide-sensitive factor attachment protein receptor (SNARE) protein expression, phosphorylated Akt S473 and P70S6K1 T389, and glucose transporter 2 (GLUT2) expression were also identified in MIP-βIRKO HFD islets. Overall, the postnatal knockout of beta cell IR in HFD-fed mice resulted in decreased expression of beta cell glucose-sensing and exocytotic proteins and a reduction in intracellular signalling. These findings highlight that IR expression in the adult islet is required to maintain beta cell function under hyperglycemic stress. Highlights: IR loss in adult beta cells led to glucose intolerance in mice fed a high-fat diet. IR loss beta cells displayed low levels of GLUT2 and exocytosis proteins. Decreased PI3K-Akt signalling was identified in IR knockout islets. Beta cell mass was unaffected by IR loss in mice.